The effect of 4-octyl itaconate on lipopolysaccharide-induced murine calvarial osteolysis - WEN Congpeng; TONG Wuyou; CHEN Xuzhuo; LAI Linfeng (Kouqiang hemian waike zazhi)
[Objective:] To investigate the effect of 4-octyl itaconate (4-OI) on lipopolysaccharide (LPS)-induced calvarial osteolysis in mice. [Methods:] CCK-8 assay was used to evaluate the effect of different concentrations of 4-OI on the cell viability of RAW 264.7 macrophages and murine primary bone marrow-derived macrophages (BMMs). Real-time quantitative polymerase chain reaction (RT-qPCR), immunofluorescence staining, and intracellular reactive oxygen species (ROS) detection kit (DCFH-DA) were used to explore the effect of 4-OI at different concentrations (12.5 µmmol/L and 50 µmmol/L) on the inflammatory response of macrophages. Tartrate-resistant acid phosphatase (TRAP) staining was used to explore the effect of 4-OI on osteoclast differentiation. The murine LPS-induced mouse calvarial osteolysis model was established, and the therapeutic effect of 4-OI on inflammatory osteolysis was evaluated by micro-CT and histological staining. [Results:] The results of CCK-8 showed that 4-OI below a concentration of 50 µmmol/L had no obvious cytotoxicity to RAW 264.7 macrophages and murine BMMs. RT-qPCR and immunofluorescence results showed that 4-OI was concentration-dependent, and inhibited the expression of pro-inflammatory cytokines. TRAP staining showed that 4-OI effectively inhibited the osteoclast differentiation induced by receptor activator of nuclear factor κB ligand (RANKL). Micro-CT and histological staining demonstrated that 4-OI effectively alleviated the inflammatory response and bone resorption around the osteolysis site. [Conclusion:] 4-OI can effectively inhibit inflammatory osteolysis, and it has great potential application in the treatment of osteolysis related diseases in oral and maxillofacial region.